Potensi Ekstrak Biji Pangi (Pangium edule Reinw) sebagai Pengawet Alami Pada Ikan Mujair (Oreochromis mossambicus) - Iren Natalia Simanjuntak; Rudi Alexander Repi; Emma Mauren Moko; Meity Nelltje Tanor; Debby Jacqueline Jochebed Rayer (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Mujair fish (Oreochromis mossambicus) is a freshwater fish that is commonly consumed. This is due that they are easily found and obtrained and with a price in fresh markets that are relatively cheap. Unfortunately, this fish happens to be a very perishable commodity, due to it’s sensitiveness to spoilage because of its high protein content and moisture content. Pangi seeds (Pangium edule) is known to contain tanines, natural polyphenols that inhibits microorganisms through their cell wall permeability. The purpose of this research was to test the potential of pangi seeds crude extract as natural pangi seed toxiti preservatives on mujair fish, shelf life potential on mujair fish. This was achieved by marinating the fish in crude pangi seed extracts at concentrations of 0% (control), 5% and 10% and then store for 4 days at room temperature. Parameters tested on this research includes cyanide identification BSLT toxicity testing and fish spoilage (degradation) through protein changes and pH. Results of this research indicated that pangi seeds crude extract does not contain any cyanide of whatsoever, pangi seed crude extract toxicity testing indicated thatit was not toxic to a concentration of 128233mg/L, meanwhile protein analysis indicated that the optimum concentration of pangi seed crude extract to inhibit fish spoilage is 10% while in terms of pH degradation, the optimum concentration was 5%.